KARNINI YONIVYAPAD W.S.R TO CERVICAL EROSION – A CASE STUDY - Richa Tiwari; Buduru, Pushpalatha; Bharathi K (AYUSHDHARA, 2021)
Karnini Yonivyapad is described with its own pathogenesis and treatment in classical text. It can be compared with cervical erosion due to its clinical appearance. Among all Yonivyapad, only this Yonivyapad is related with cell pathology. In present circumstances when cervical intraepithelial neoplasia, cervical cancer are the burning issues in front of whole world, it is necessary to understand physiology and pathology of cervix in benign stages so that an appropriate prevention or treatment can be done at this stage. An ideal and complete treatment of pathological erosion should be that which destroy the ectopic columnar epithelium and make healthy cell environment so that regression of erosion will take place properly. Virechana karma is the radical purification that eliminates waste products, toxins and aggravated doshas from the body. As aggravated Doshas are the primary cause of disease, this method is the most direct for curative purposes. In present study, patient with Karnini yonivyapada is treated with combination of Shodhan, shaman and local therapy. Trivrit Lehya has been selected for Virechana karma because in all the herbs easy and safe among purgative is Trivrit. Apamarga (Achyranthes aspera L.) kshar Tail used for Yoni pichu and Triphala Guggul is selected for Shaman chikitsa, which is seen to be very much effective.